Retro rectus mesh repair for umbilical hernia in adults: a study of 50 cases - Vagholkar, Ketan (International Surgery Journal, 2019)
Background: Umbilical hernia is one of the most commonly encountered hernia in surgical practice. A variety of repairs have been tried our ranging from open to laparoscopic. However controversy still persists as to which type of repair is the gold standard for umbilical hernia. Open technique comprises of the onlay mesh repair which is known to develop a variety of complications. Even laparoscopic approach also has failure rates as well as local complications. The aim of the study was to evaluate the surgical outcome of open retro rectus mesh repair for adult umbilical hernias. Methods: 50 consecutive cases of umbilical hernia were repaired by open technique with retro rectus placement of mesh. Results: There were no local complications or any recurrence in any of the fifty patients. Conclusions: Retro rectus placement of mesh in open repair of umbilical hernia in adults is a safe and effective modality of treatment.